Corrections and emendations to the description of Deltamys araucaria Quintela et al., 2017 (Rodentia, Cricetidae) - Pardiñas, Ulyses F. J. (Zootaxa, 2018)
A new species was recently described to the akodontine genus Deltamys Thomas, 1917, based on animals collected in Araucaria forest, Rio Grande do Sul state, Brazil. Quintela et al. (2017) described Deltamys araucaria on the basis of the integration of morphological, chromosomal, and molecular characters analysis. Here I correct and/or emend critical aspects of this paper, including the type locality, diagnostic characters, and the appropriate recognition of earlier literature on this same taxon. My aim in this note is not to criticize this important new contribution but to facilitate future communication among researchers.